Excessive smartphone use and its correlations with social anxiety and quality of life among medical students in a public university in Malaysia: A cross-sectional study - Mohd Salleh Sahimi, Hajar; Norzan, Mohd Hafiz; Nik Jaafar, Nik Ruzyanei; Sharip, Shalisah; Ashraf, Ammar; Shanmugam, Kamaleshini; Bistamam, Nur Shahirah; Mohammad Arrif, Najat Emir; Kumar, Saathish; Midin, Marhani (Frontiers in Psychiatry, 2022)
Introduction Smartphone usage has significantly increased in the last decade among young adults has significantly increased in the last decade. While its benefits are undeniable, its negative implications are increasingly emerging. Studies are needed to investigate the effects of excessive smartphone use on a young person's life. This study aimed to determine the prevalence of excessive smartphone use among medical students and its relations with social anxiety, self-esteem, and quality of life. Methods A cross-sectional study was conducted among medical students from Universiti Kebangsaan Malaysia (UKM) in UKM Medical Center. A total of 273 students have consented to participate and completed self-reported questionnaires encompassing sociodemographic information, the Short Version Smartphone Addiction Scale (SAS-SV), the Social Interaction Anxiety Scale (SIAS), the World Health Organization Quality of Life (WHOQOL-BREF) and the Rosenberg Self-esteem Scale (RSES). Sociodemographic data, SIAS score, WHOQOL-BREF score and the Rosenberg Self-esteem Scale score were treated as independent variables. Smartphone addiction Scale score was treated as the dependent variable. Bivariate analysis was used to explore the relationship between independent and dependent variables using the Fisher exact test, Pearson Chi-Square and Pearson correlation coefficient. Multiple linear regression analysis was used to analyze the variables with a p-value of < 0.05 from the Pearson correlation coefficient test. Results The percentage of excessive smarphone use among UKM medical students is 48%. The bivariate analysis showed that excessive smartphone use has a small but significant positive correlation with social anxiety (r = 0.173, p = 0.004) and negative correlations with physical health (r = −0.133, p = 0.028), psychological wellbeing (r =−0.135, p = 0.026), social relationships (r = −0.232, p = 0.001), environment (r = −0.260, p = 0.001) and self-esteem (r = −0.128, p = 0.035). In the multiple regression analysis, a better environment predicted a reduced risk for smartphone addiction (β = −0.233, p = 0.013). Conclusion Almost half of the students were found to have smartphone overdependence. Excessive smartphone use has shown a significant relationship with an increased risk for social anxiety, reduction in self-esteem, and quality of life among medical students. A closer look into the possible intervention is needed in the future to curb the negative effects arising from excessive smartphone use.